Linear porokeratosis with multiple squamous cell carcinomas successfully treated by electrochemotherapy. (1st December 2016) - Sommerlad, M.; Lock, A.; Moir, G.; McGregor, J.; Bull, R.; Cerio, R.; Harwood, C.
Summary: Porokeratosis is a clonal epidermal disorder of keratinization characterized by annular lesions with an atrophic centre and a hyperkeratotic edge. The cornoid lamella is the histopathological hallmark. Six clinical variants are recognized: porokeratosis of Mibelli; disseminated superficial porokeratosis; disseminated superficial actinic porokeratosis (DSAP); porokeratosis plantaris et palmaris disseminata; punctate porokeratosis and linear porokeratosis. Linear porokeratosis is the type most frequently associated with malignant transformation into squamous cell carcinoma (SCC). It is thought to represent a mosaic form of DSAP and has an incidence of less than 1 in 200 000; treatment options are limited. We describe a patient with systematized linear porokeratosis and multiple SCCs who was successfully treated with bleomycin electrochemotherapy (ECT), a form of intralesional chemotherapy. In view of their large number, the individual SCCs were treated with bleomycin ECT. One year post‐treatment the patient remains tumour free. To our knowledge, this is the first case of multiple SCCs treated by ECT in the context of systematized linear porokeratosis. Our case highlights the challenges associated with diagnosing and managing this unusual form of porokeratosis.